Perception of Mandarin tones across different phonological contexts by native and tone-naive listeners - Vonessen, Jules; Zellou, Georgia (Frontiers in Education, 2024)
Coarticulation is a type of speech variation where sounds take on phonetic properties of adjacent sounds. Listeners generally display perceptual compensation, attributing coarticulatory variation to its source. Mandarin Chinese lexical tones are coarticulated based on surrounding tones. We tested how L1-Mandarin and naive listeners compensate for tonal coarticulation using a paired discrimination task. L1 listeners showed greater perceptual sensitivity to tonal differences than tonenaive listeners. Yet, both L1 and tone-naive listeners showed differences in sensitivity to differentlycoarticulated versions of the rising tone presented in the same tonal context. In different tonal contexts, both groups showed similar patterns of perceptual compensation for tonal coarticulation. Thus, although L1 and naive Mandarin listeners show different sensitivities to tonal variation, they display similar compensatory patterns for tonal coarticulation.